The free-market innovation machine : analyzing the growth miracle of capitalism - Baumol, William J. (Princeton University Press, 2004)
Why has capitalism produced economic growth that so vastly dwarfs the growth record of other economic systems, past and present? Why have living standards in countries from America to Germany to Japan risen exponentially over the past century? William Baumol rejects the conventional view that capitalism benefits society through price competition--that is, products and services become less costly as firms vie for consumers. Where most others have seen this as the driving force behind growth, he sees something different--a compound of systematic innovation activity within the firm, an arms race in which no firm in an innovating industry dares to fall behind the others in new products and processes, and inter-firm collaboration in the creation and use of innovations.